PENGEMBANGAN METODE SOSIODRAMA DAN MEDIA AUDIO VISUAL (FILM PENDEK) DALAM MENUMBUHKAN SIKAP BERAGAMA SISWA DI SMA NEGERI 5 REJANG LEBONG - Widiya Suherni (UIN Fatmawati Sukarno Bengkulu, 2019)
This research is motivated by the fact that Islamic Education teachers play an important role in fostering students to have a religious attitude. There are several methods that can be used in fostering a religious attitude towards students, one of them is the sociodrama method. In addition, the use of audio visual media (short films) is the most appropriate media to foster a religious attitude towards students. The purpose of this study is to reveal about: 1) PAI material that can be explained using a combination of sociodrama learning methods and Audio Visual media (short films). 2) The process of conducting the incorporation of sociodramas and Audio Visual media (short films) in fostering a religious attitude towards students. 3) Supporting and inhibiting factors for the application of a combination of sociodrama methods and Audio Visual media (short films). This study uses a qualitative approach. The researcher used triangulation as a technique to check the validity of the data. Where in the sense of triangulation is a technique of checking the validity of data that uses something else in comparing the results of interviews with the object of research. Data analysis uses descriptive non-statistical analysis method which includes inductive thinking, ie researchers depart from specific knowledge to assess a common event. The results of the study on the incorporation of sociodramatic methods and audio-visual media (short films) are: 1) Appropriate PAI material is material that is applicative or directly related to the daily social life of students. In this case, the matching class of SMA XI PAI uses a combination of sociodrama methods and audio-visual media (short films) is material for comfortable living with honest behavior and concern for Muslims towards the corpse. 2) The process of combining sociodrama methods and audio visual media (short films) through several stages, namely; selection of material, preparing short films and sociodrama scenarios, screenings in the classroom, drawing conclusions, stabilizing material with sociodrama methods, drawing conclusions and evaluating. 3) Supporting factors for the incorporation of sociodrama methods and audio visual media (short films) are the spirit, determination, views, understanding and teaching experience of PAI teachers. The inhibiting factors for the implementation are: time allocation, shy students, not all materials can use the sociodrama method and if the sociodrama goes not as expected then the learning objectives are not achieved.